Dynamics of a revised neural mass model in the stop-signal task. (October 2020) - Ye, Weijie
Highlights: A Jansen-Rit model is revised to adapt the population activities of stop-signal task. We combine equilibrium points and manifolds with the task behaviors to explain dynamical mechanism of stopping a saccade. We propose a dynamical mechanism to explain how bistability affects the rhythmic change of task performance. Abstract: Stopping a planned action is an important form of inhibitory control. In this work, we revise a Jansen-Rit model to adapt the stop-signal task in order to research the dynamical mechanisms of inhibitory control in this task. Firstly, the revised model successfully simulates the population activities of the stop-signal task and the reaction time distribution in experimental results. Secondly, the consequences of single-parameter bifurcation analysis exhibit that the activity of successful stop-signal task corresponds to the upper stable equilibrium point with a high population firing rate and the response of non-cancelled stop-signal task corresponds to the lower stable equilibrium point with a low population firing rate. Additionally, the model shows bistability which simultaneously exists the upper and lower stable equilibrium points. This bistability induces the rhythmic change of the saccade probability as the stop signal intensity and stop signal delay vary. Combining the phase space analysis and the task performances, we conclude a dynamical mechanism to account for the variation of the saccade probability. Finally, two-parameters bifurcation analysis is performed to investigate the dynamics in go signal intensity and stop signal intensity plane. We find that the fold curves divide the plane into one bistability area and two monostability areas, indicating that distinct ratios of the go signal intensity and stop signal intensity can result in different behavior modes of the task.